2015
DOI: 10.1007/s11274-015-1902-6
|View full text |Cite
|
Sign up to set email alerts
|

Mini review: hydrogen and ethanol co-production from waste materials via microbial fermentation

Abstract: The simultaneous production of hydrogen and ethanol by microorganisms from waste materials in a bioreactor system would establish cost-effective and time-saving biofuel production. This review aims to present the current status of fermentation processes producing hydrogen accompanied by ethanol as a co-product. We outlined the microbes used and their fundamental pathways for hydrogen and ethanol fermentation. Moreover, we discussed the exploitation of renewable and sustainable waste materials as promising feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Apart from this, palm oil mill effluent which is one of the biggest problems in Malaysia (Embrandiri et al 2015) has energy potential of 20.23 Mtoe (Ng et al 2012). Likewise, biomass energy potential of Sweden from municipal waste is 56 PJ/yr, whereas from agricultural solid waste it is 237 PJ/yr (Wiesenthal and Mourelatou 2006;Skovgaard et al 2008). The above section highlights that there is a tremendous potential of energy generation stored in waste.…”
Section: Global Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from this, palm oil mill effluent which is one of the biggest problems in Malaysia (Embrandiri et al 2015) has energy potential of 20.23 Mtoe (Ng et al 2012). Likewise, biomass energy potential of Sweden from municipal waste is 56 PJ/yr, whereas from agricultural solid waste it is 237 PJ/yr (Wiesenthal and Mourelatou 2006;Skovgaard et al 2008). The above section highlights that there is a tremendous potential of energy generation stored in waste.…”
Section: Global Scenariomentioning
confidence: 99%
“…Likewise, biohydrogen is also being produced by decomposing carbohydrate-rich waste material through this simple technology. Biohydrogen could be produced either by dark fermentation or through photo-fermentation (Ntaikou et al 2010;Chaubey et al 2013;Soo et al 2015). At the end of the fermentation process, alcohol solvents and organic acids are produced apart from hydrogen which can also be commercially utilized instead of being discharged as waste.…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous production of hydrogen and ethanol from waste materials has the potential for the development of a more cost-effective biofuel generation process. Their co-production is more beneficial in terms of cost and time savings compared to fermentation focusing on either hydrogen or ethanol production alone [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, very little research has been conducted with the aim of optimizing the simultaneous production of hydrogen and ethanol from CG fermentation at the same time. Mostly, studies were conducted with pure culture [5,18,19] and engineered strains [20,21]. Recently, two studies reported the production of hydrogen and ethanol from CG by mixed culture fermentation [22,23].…”
Section: Introductionmentioning
confidence: 99%